A Comprehensive Analysis on Interference Avoidance for Dynamic Spectrum Sharing between FDD LTE and NR. (18th January 2022) - Wang, Jun; Mu, Dejun
Abstract : This paper presents a comprehensive analysis on the interference avoidance for dynamic spectrum sharing (DSS) between FDD LTE and NR to solve the coverage layer for NR standalone (SA) network with low FDD LTE bands. In the first place, detailed collisions between FDD LTE and NR are presented and involved with physical control channel, physical data channel, and physical signal of both downlink and uplink. The corresponding principle of collision avoidance is also proposed based on the flexible configuration of NR physical layer in both the time domain and the frequency domain. Due to LTE CRS across the whole bandwidth, the collide with LTE CRS cannot be fully avoided by flexible configuration and need LTE CRS puncturing or NR puncturing on these collided LTE CRS with DSS activation. However, both LTE CRS puncturing and NR puncturing more or less cause the impacts on the performance. As with NR puncturing for LTE CRS, the simulation analysis on the impacts of NR SSB and RMSI is presented. On the other hand, LTE CRS puncturing influences the reception performance of LTE UE, and we analyze the impact of RSRP measurement, demodulation, and frequency/time offset measurement by simulation. Finally, capacity loss also is explained based on essential overhead.